2011
DOI: 10.1002/alr.20020
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and efficacy of a novel bioabsorbable, steroid‐eluting sinus stent

Abstract: This study demonstrates the safety and efficacy of a novel bioabsorbable, steroid-eluting stent for use in CRS patients. The steroid-eluting stent is effective in improving wound healing by preserving sinus patency, reducing inflammation, and minimizing adhesions via controlled local steroid delivery without measurable systemic exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
240
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(260 citation statements)
references
References 43 publications
14
240
0
4
Order By: Relevance
“…There was also no significant corticosteroid systemic absorption or ocular toxicity. 1307,1317,1318 A meta-analysis combined the results from the 2 RCTs to demonstrate statistically significant reductions in the need for postoperative intervention, oral corticosteroid usage, polyposis, and adhesions. 1319 An economic evaluation also demonstrated that Propel TM is cost-effective in decreasing postoperative intervention.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…There was also no significant corticosteroid systemic absorption or ocular toxicity. 1307,1317,1318 A meta-analysis combined the results from the 2 RCTs to demonstrate statistically significant reductions in the need for postoperative intervention, oral corticosteroid usage, polyposis, and adhesions. 1319 An economic evaluation also demonstrated that Propel TM is cost-effective in decreasing postoperative intervention.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…However, few studies have focused on patient-reported QOL outcomes with the use of this device, and the relative efficacy in the treatment of different phenotypes of CRS has not been analyzed in previous studies [6][7][8]12]. The goal of this study was to determine if a bioabsorbable steroid-eluting implant would have a differential effect on patient-reported QOL relative to the status of baseline eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Topical intranasal steroids can minimize systemic effects and are an integral component in treatment; however, penetration into the middle meatus and sinus cavities can be limited by postoperative edema and crusting [7]. Current efforts are focused on improving steroid delivery to the diseased sinuses while limiting their systemic effects [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations